Compostos orgânicos voláteis emitidos por Fusarium oxysporum apresentam atividade nematicida - Terra, Willian César (2016)
A series of assays was carried out aiming to understand the nematicidal activity of the volatile organic compounds (VOCs) emitted by Fusarium oxysporum isolated 21 (Fo-21) on plant-parasitic nematodes. Through analysis by gas chromatography coupled to mass spectrometry (GC-MS) 50 compounds were detected in the Fo-21 emission. The main classes of compounds emitted by Fo-21 were sesquiterpenes, esters and alcohols. Water exposed to VOCs caused 100% immobility in second-stage juveniles (J 2) of Meloidogyne incognita. In addition, inoculation of those J2 in tomato decreased infectivity up to 70% and reproduction up to 65%. Application of water exposed to VOCs in substrate infested with M. incognita J 2 resulted in 56% reduction in number of galls and 49% in number of eggs. The eight most abundant VOCs emitted by F.o–21 were tested against M. incognita and Heterodera schachtii. Compounds 2– methylbutyl acetate (1), 3-methylbutyl acetate (2), ethyl acetate (7) and, 2-methylpropyl acetate (8), caused in vitro mortality of 100%, 92.5%, 100% and 83.8%, respectively, in M. incognita and 90.0%, 88.8%, 96.3% and 97.5% mortality, respectively, on H. schachtii J 2, when tested at a concentration of 500 µg.ml -1 . The lethal concentration (LC50) for compounds 1, 2, 7 and 8, in M. incognita J 2 was of 236, 198, 213 and 218 µg.ml -1 , respectively. Under the same conditions, the commercial nematicide carbofuran (2,3-dihydro-2,2-dimethyl-1-benzofuran-7-yl N-methylcarbamate) showed a LC50 of 191 µg.ml -1 . Eggs exposed to compounds 1, 2, 7 and 8, for 72 h showed a reduction in hatching of 36.5%, 55.2%, 91.0% and 10.3%, respectively, and reduction in infectivity of 53.0%, 53.0%, 32.0 % and 39.0%, respectively. When compounds were applied in tomato seedlings infested by M. incognita, compound 1 reduced the number of galls per gram of root in 27.5% when compared to the negative control (without the application of nematicide).